Dielectric Coating
By using an insulating coating composed of powder coatings and a high thermal conductivity adhesive layer in the heat transfer system, the problem of difficult to manage structural integrity and thermal management in the prior art is solved, and the comprehensive effect of high voltage insulation and high thermal conductivity is achieved.
Patent Information
- Application Number
- JP2023132800
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-17
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2043-08-17
AI Technical Summary
The prior art is difficult to effectively manage structural integrity and thermal management in heat transfer systems, especially in the case of high voltages and high heat flow.
Using an insulating coating composed of a powder coating and a high thermal conductivity adhesive layer, the insulating coating composed of a powder coating provides high voltage insulation performance, and the heat conduction efficiency is improved through the adhesive layer with a high thermal conductivity.
Structural integrity and thermal management under high voltage and high heat flow conditions are achieved, providing insulation strength up to 50 kV/mm and thermal conductivity ranges from 0.3 W/K.m to 2.5 W/K.m.
Smart Images

Figure 0007659600000003 
Figure 0007659600000004 
Figure 0007659600000005
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to PCT Application No. PCT / CN2022 / 113045, entitled "Dielectric Coatings," filed August 17, 2022, and incorporated by reference in its entirety herein.
[0002] Field The present disclosure is directed to dielectric coatings, systems for coating substrates, methods for coating substrates, and coated substrates. [Background technology]
[0003] background Coatings, including those formed from powder coating compositions, and adhesives are utilized in a wide variety of applications, including use as interface materials to manage structural integrity and thermal management in heat transfer systems. Summary of the Invention [Means for solving the problem]
[0004] overview A coated substrate comprising a coating layer and an adhesive formed on at least a portion of the coating layer, the coating layer being deposited from a powder coating composition and having a dielectric strength of at least 50 kV / mm, e.g., at least 60 kV / mm, e.g., 120 kV / mm or less, e.g., 100 kV / mm or less, e.g., from 50 kV / mm to 120 kV / mm, e.g., from 60 kV / mm to 100 kV / mm, measured according to ASTM D149-09 (voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall), and a dielectric strength of at least 50 kV / mm, e.g., at least 60 kV / mm, e.g., 120 kV / mm or less, e.g., 100 kV / mm or less, e.g., from 50 kV / mm to 120 kV / mm, e.g., from 60 kV / mm to 100 kV / mm, measured according to ASTM and an adhesive is formed from the adhesive composition and has a thermal conductivity measured according to ASTM D5470 (steady state method) of at least 0.7 W / Km, such as at least 0.8 W / Km, for example at least 0.9 W / Km, such as at least 1.0 W / Km, for example at least 1.5 W / Km, such as at least 2.5 W / Km, for example at least 2.0 W / Km, for example at least 0.7 W / Km, such as at least 0.8 W / Km, for example at least 0.9 W / Km, for example at least 1.0 W / Km, such as at least 1.5 W / Km, for example at least 2.5 W / Km, for example at least 2.0 W / Km, for example at least 0.7 W / Km, such as at least 0.8 W / Km, for example at least 0.9 W / Km, for example at least 1.0 W / Km, such as at least 1.5 W / Km, Disclosed herein is a coated substrate comprising a thermal conductivity of 5 W / Km, such as from 1.0 W / Km to 2.5 W / Km, for example, from 1.5 W / Km to 2.5 W / Km, for example, from 0.7 W / Km to 2.0 W / Km, for example, from 0.8 W / Km to 2.0 W / Km, for example, from 0.9 W / Km to 2.0 W / Km, for example, from 1.0 W / Km to 2.0 W / Km, for example, from 1.5 W / Km to 2.0 W / Km.
[0005] Also disclosed herein is a system for coating a substrate comprising a powder coating composition including an electrically insulating filler and an adhesive coating composition including a thermally conductive filler, wherein the two layers, when deposited on a substrate and cured, have a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured using a TIM Heat Resistance and Conductivity Measuring Instrument (Model LW-9389) according to ASTM D5470 (Steady State Method).
[0006] Also disclosed is a method of coating a substrate, the method including applying a powder composition onto a surface of the substrate to form a coating, and applying an adhesive composition to at least a portion of the coating to form an adhesive. In one embodiment, for example, the following items are provided: (Item 1A) 1. A coated substrate comprising a coating layer and an adhesive formed on at least a portion of the coating layer, the coating layer being deposited from a powder coating composition and having a dielectric strength of at least 50 kV / mm, e.g., at least 60 kV / mm, e.g., 120 kV / mm or less, e.g., 100 kV / mm or less, e.g., from 50 kV / mm to 120 kV / mm, e.g., from 60 kV / mm to 100 kV / mm, measured according to ASTM D149-09 (voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall), and ... D5470 (steady state method), the adhesive is formed from an adhesive composition and has a thermal conductivity of at least 0.7 W / Km, such as at least 0.8 W / Km, for example at least 0.9 W / Km, such as at least 1.0 W / Km, for example at least 1.5 W / Km, such as at least 2.5 W / Km, for example at least 2.0 W / Km, for example at least 0.7 W / Km, such as at least 0.8 W / Km, for example at least 0.9 W / Km, such as at least 1.0 W / Km, for example at least 1.5 W / Km, The coated substrate comprising a thermal conductivity of 0.7 W / Km to 2.0 W / Km, for example, 0.8 W / Km to 2.0 W / Km, such as, for example, 0.9 W / Km to 2.0 W / Km, for example, 1.0 W / Km to 2.0 W / Km, for example, 1.5 W / Km to 2.0 W / Km. (Item 2A) the coating comprises a dielectric breakdown of at least 12 kV / mm, e.g., at least 15 kV / mm, e.g., at least 20 kV / mm, e.g., at least 25 kV / mm, e.g., at least 30 kV / mm, measured according to ASTM D149-09 (voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall); and / or the adhesive comprises a lap shear strength of at least 3 MPa, such as at least 8 MPa, for example, 30 MPa or less, such as 12 MPa or less, for example, 3 MPa to 30 MPa, for example, 8 MPa to 12 MPa, measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up rate of 1 mm / min. (Item 3A) 2. The coated substrate according to any one of the preceding items, wherein the coating layer comprises a dry film thickness of 50 microns, such as at least 75 microns, for example at least 100 microns, such as 300 microns or less, for example 250 microns or less, such as 220 microns or less, for example 200 microns or less, such as from 50 microns to 300 microns, for example from 75 microns to 250 microns, such as from 100 microns to 220 microns, for example from 100 microns to 200 microns. (Item 4A) 2. The coated substrate according to any one of the preceding items, wherein the adhesive layer comprises a dry film thickness of at least 0.2 mm, such as at least 0.3 mm, for example at least 0.4 mm, such as 3.0 mm or less, for example 1.5 mm or less, such as 1.0 mm or less, for example from 0.2 mm to 3.0 mm, such as from 0.3 mm to 1.5 mm, for example from 0.4 mm to 1.0 mm. (Item 5A) 2. The coated substrate according to any one of the preceding items, wherein the adhesive composition comprises a thermally conductive filler in an amount of at least 60 wt%, such as at least 75 wt%, for example up to 90 wt%, such as up to 86 wt%, for example from 60 wt% to 90 wt%, for example from 75 wt% to 86 wt%, based on the total weight of the adhesive composition. (Item 6A) 10. The coated substrate according to any one of the preceding items, wherein the powder composition comprises an electrically insulating filler in an amount of at least 30% by weight, such as at least 45% by weight, for example at least 50% by weight, such as 60% by weight or less, for example 55% by weight or less, for example 50% by weight or less, such as 30% to 60% by weight, for example 45% to 55% by weight, such as 45% to 55% by weight, for example 45% to 50% by weight, for example 50% to 55% by weight, based on the total weight of the powder composition. (Item 7A) 2. The coated substrate of any one of the preceding claims, wherein the adhesive composition further comprises a non-thermally conductive filler, an electrically insulating filler, a flame retardant filler, or any combination thereof. (Item 8A) 2. The coated substrate of any one of the preceding claims, wherein the powder composition further comprises a thermally conductive filler, a non-thermally conductive filler, a flame retardant filler, or any combination thereof. (Item 9A) 2. The coated substrate of any one of the preceding claims, wherein the adhesive composition further comprises a compound containing an electrophilic functional group, a thiol-terminated compound, a thermoplastic polymer, or any combination thereof. (Item 10A) 2. The coated substrate of any one of the preceding claims, wherein the powder composition further comprises a film-forming resin comprising a (meth)acrylate resin, a polyurethane, a polyester, a polyamide, a polyether, a polysiloxane, an epoxy resin, a vinyl resin, a copolymer thereof, or any combination thereof. (Item 11A) 13. The coated substrate of any one of the preceding claims, wherein the substrate is part of an electrical storage device. (Item 12A) 8. The coated substrate of any one of the preceding claims, wherein the power storage device comprises a battery or a battery component. (Item 13A) 2. The coated substrate of any one of the preceding items, wherein the battery or battery component comprises a battery cell, a battery shell, a battery module, a battery pack, a battery box, a battery cell casing, a pack shell, a battery lid and tray, a thermal management system, a battery housing, a module housing, a module racking, a battery side plate, a battery cell enclosure, a cooling module, a cooling tube, a cooling fin, a cooling plate, a bus bar, a battery frame, an electrical connection, a metal wire, a copper or aluminum conductor or cable, or any combination thereof. (Item 14A) 7. The coated substrate of any one of the preceding claims, further comprising a second substrate in contact with the adhesive. (Item 15A) 2. The coated substrate of any one of the preceding claims, wherein the first substrate is a cooling plate and the second substrate is a battery cell. (Item 16A) 2. The coated substrate of any one of the preceding items, wherein the coated substrate has a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured according to ASTM D5470 (Steady State Method) using a TIM Heat Resistance and Conductivity Measuring Apparatus (Model LW-9389). (Item 17A) 1. A system for coating a substrate comprising a powder coating composition comprising an electrically insulating filler and an adhesive coating composition comprising a thermally conductive filler, wherein the two layers, when deposited on a substrate and cured, have a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured using a TIM Heat Resistance and Conductivity Measuring Instrument (Model LW-9389) according to ASTM D5470 (Steady State Method). (Item 18A) The system of the preceding paragraph, wherein the adhesive layer, when deposited and cured, has a lap shear strength of at least 3 MPa, e.g., 3 MPa to 30 MPa, e.g., 8 MPa to 12 MPa, measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up speed of 1 mm / min. (Item 19A) 11. The system of claim 1, wherein the adhesive composition comprises 60% to 90% by weight, for example 75% to 86% by weight, of the thermally conductive filler, based on a total weight of the adhesive composition. (Item 20A) 2. The system of claim 1, wherein the powder composition comprises 30% to 90% by weight, for example 45% to 55% by weight, of an electrically insulating filler, based on the total weight of the powder composition. (Item 21A) 2. The system of any one of the preceding claims, wherein the adhesive composition further comprises a non-thermally conductive filler, an electrically insulating filler, and / or a flame retardant filler. (Item 22A) 2. The system of any one of the preceding claims, wherein the powder composition further comprises a thermally conductive filler, a non-thermally conductive filler, and / or a flame retardant filler. (Item 23A) 2. The system of any one of the preceding claims, wherein the adhesive composition further comprises a compound containing an electrophilic functional group, a thiol-terminated compound, a thermoplastic polymer, or any combination thereof. (Item 24A) 2. The system of any one of the preceding claims, wherein the powder composition further comprises a film-forming resin comprising a (meth)acrylate resin, a polyurethane, a polyester, a polyamide, a polyether, a polysiloxane, an epoxy resin, a vinyl resin, a copolymer thereof, or any combination thereof. (Item 25A) 1. A method of coating a substrate, the method comprising: applying a powder composition onto a surface of the substrate to form a coating; and applying an adhesive composition to at least a portion of the coating to form an adhesive. (Item 26A) The method of the preceding item, wherein the coating layer is formed via a multi-application process. (Item 27A) 13. The method of any one of the preceding items, wherein the powder composition is at least partially cured prior to application of the adhesive composition. (Item 28A) The method of any one of the preceding items, wherein the resulting coated substrate comprises any of the coated substrates of any one of the preceding items. (Item 29A) A battery comprising a battery cell and the coated substrate of any one of the preceding items. (Item 30A) 13. The battery of the preceding item, wherein the battery cells and the coating are housed in a module. (Item 31A) 7. The battery of any one of the preceding claims, wherein the battery and the coating are housed in a pack. (Item 32A) 13. The battery of any one of the preceding claims, wherein the modules are housed in a pack. (Item 33A) vehicle 7. The battery of any one of the preceding claims adjacent to a chassis of the vehicle. (Item 34A) 7. The battery of any one of the preceding claims, further comprising a battery component. (Item 35A) Comprising a battery according to any one of the preceding items, vehicle . (Item 36A) The above vehicle But on land vehicle , an aircraft, or a bicycle, such as an electric bicycle, vehicle . In another embodiment, for example, the following items are provided: (Item 1B) 1. A coated substrate comprising a coating layer and an adhesive formed on at least a portion of the coating layer, the coating layer being deposited from a powder coating composition and having a dielectric strength of at least 50 kV / mm measured in accordance with ASTM D149-09 (voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) and at least 0.3 W / K measured in accordance with ASTM D5470 (steady state method). . m, said adhesive being formed from an adhesive composition and having a thermal conductivity of at least 0.7 W / K measured in accordance with ASTM D5470 . The coated substrate, including its thermal conductivity of m. (Item 2B) 10. The coated substrate of claim 1, wherein the coating comprises a dielectric breakdown of at least 12 kV / mm measured according to ASTM D149-09 (voltage limits of 12.0 kV DC, Imax limits of 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall), the adhesive comprises a dielectric breakdown of at least 6 kV / mm measured according to ASTM D149-09 (voltage limits of 12.0 kV DC, Imax limits of 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall), and / or the adhesive comprises a lap shear strength of at least 3 MPa measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up rate of 1 mm / min. (Item 3B) 2. The coated substrate of any one of the preceding claims, wherein the adhesive composition comprises a thermally conductive filler and / or the powder composition comprises an electrically insulating filler. (Item 4B) 13. The coated substrate of any one of the preceding claims, wherein the substrate is part of an electrical storage device. (Item 5B) 8. The coated substrate of any one of the preceding claims, wherein the power storage device comprises a battery or a battery component. (Item 6B) 7. The coated substrate of any one of the preceding claims, further comprising a second substrate in contact with the adhesive. (Item 7B) 2. The coated substrate of any one of the preceding items, wherein the coated substrate has a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured according to ASTM D5470 (Steady State Method) using a TIM Heat Resistance and Conductivity Measuring Apparatus (Model LW-9389). (Item 8B) 1. A system for coating a substrate comprising a powder coating composition comprising an electrically insulating filler and an adhesive coating composition comprising a thermally conductive filler, wherein the two layers, when deposited on a substrate and cured, have a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured using a TIM Heat Resistance and Conductivity Measuring Instrument (Model LW-9389) according to ASTM D5470 (Steady State Method). (Item 9B) The system of the preceding paragraph, wherein the adhesive layer, when deposited and cured, has a lap shear strength of at least 3 MPa, e.g., 3 MPa to 30 MPa, e.g., 8 MPa to 12 MPa, measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up speed of 1 mm / min. (Item 10B) The adhesive composition comprises: (a) containing 60% by weight to 90% by weight of the thermally conductive filler based on the total weight of the adhesive composition; (b) further comprising a non-thermally conductive filler, an electrically insulating filler, and / or a flame retardant filler; and / or The system of any one of the preceding claims, further comprising (c) an electrophilic functional group, a thiol-terminated compound, a thermoplastic polymer, or any combination thereof. (Item 11B) The powder composition comprises: (a) containing 30% by weight to 90% by weight of an electrically insulating filler based on the total weight of the powder composition; (b) further comprising a non-thermally conductive filler, an electrically insulating filler, and / or a flame retardant filler; The system of any one of the preceding items, further comprising: (c) a film-forming resin comprising a (meth)acrylate resin, a polyurethane, a polyester, a polyamide, a polyether, a polysiloxane, an epoxy resin, a vinyl resin, a copolymer thereof, or any combination thereof. (Item 12B) 1. A method of coating a substrate, the method comprising: applying a powder composition onto a surface of the substrate to form a coating; and applying an adhesive composition to at least a portion of the coating to form an adhesive. (Item 13B) The method of the preceding item, wherein the coating layer is formed via a multi-application process. (Item 14B) 13. The method of any one of the preceding items, wherein the powder composition is at least partially cured prior to application of the adhesive composition. (Item 15B) A battery comprising a battery cell and the coated substrate of any one of the preceding items. (Item 16B) 13. The battery of the preceding item, wherein the battery cells and the coating are housed in a module. (Item 17B) 7. The battery of any one of the preceding claims, wherein the battery and the coating are housed in a pack. (Item 18B) 13. The battery of any one of the preceding claims, wherein the modules are housed in a pack. (Item 19B) vehicle 7. The battery of any one of the preceding claims adjacent to a chassis of the vehicle. (Item 20B) 7. The battery of any one of the preceding claims, further comprising a battery component. (Item 21B) Comprising a battery according to any one of the preceding items, vehicle . (Item 22B) The above vehicle But on land vehicle , an aircraft, or a bicycle, vehicle . summary Disclosed herein is a coated substrate comprising a coating layer and an adhesive formed on at least a portion of the coating layer. The coating layer can be deposited from a powder coating composition and comprises a dielectric strength of at least 50 kV / mm measured according to ASTM D149-09 (voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) and a thermal conductivity of at least 0.3 W / Km measured according to ASTM D5470 (steady state method). The adhesive can be formed from an adhesive composition and comprises a thermal conductivity of at least 1.0 W / Km measured according to ASTM D5470. Also disclosed herein is a system for coating a substrate. Also disclosed is a method for coating a substrate. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram of a top-down view of a cylindrical battery cell.
[0008] [Diagram 2]FIG. 2 is a schematic exploded isometric view of an array of prismatic battery cells.
[0009] [Diagram 3] FIG. 3 is a schematic diagram of a front view of an array of pouch battery cells.
[0010] [Figure 4] FIG. 4 is a schematic isometric view of a cylindrical cell arranged within a battery module.
[0011] [Diagram 5] FIG. 5 is a schematic diagram of an exploded perspective view of a battery pack including multiple battery cells.
[0012] [Figure 6A] FIG. 6 is a schematic isometric view of (A) a battery cell, (B) a battery module, and (C) a battery pack. [Figure 6B] Same as above. [Figure 6C] Same as above.
[0013] [Figure 7] FIG. 7 is a schematic diagram of a perspective view of a battery pack.
[0014] [Figure 8] FIG. 8 is a schematic diagram of a battery pack configuration from cells.
[0015] [Figure 9] FIG. 9 is a schematic diagram of an isometric cut-out view of a cell-to-chassis battery assembly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Detailed Description For the purposes of this detailed description, it will be understood that the present disclosure may assume alternative variations and step sequences unless expressly indicated to the contrary. Moreover, in any operational examples or unless otherwise indicated, all numerical values expressing, for example, the amounts of ingredients used in the specification and claims are to be understood as being modified in all instances by the term "about". Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending on the desired properties to be obtained by the present disclosure. At the very least, and without any attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0017] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the disclosure are approximations, the numerical values set forth in the specific examples are reported as precisely as possible, however, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.
[0018] It should also be understood that any numerical range recited herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges between (and including) the recited minimum value of 1 and the recited maximum value of 10, i.e., minimum values equal to or greater than 1 and maximum values equal to or less than 10.
[0019] As used herein, the terms "including," "containing," and the like are understood to be synonymous with "comprising" in the context of this application, and therefore are open-ended and do not exclude the presence of additional undescribe or unrecited elements, materials, components, or method steps.
[0020] As used herein, "consisting of" is understood to exclude the presence of any unspecified element, component, or method step, within the context of the present application.
[0021] As used herein, "consisting essentially of" is understood in the context of this application to include the specific elements, materials, components, or method steps "and those that do not materially affect the basic and novel characteristic(s) of what is being described. As used herein, open-ended terms include closed terms such as "consisting essentially of" and "consisting of."
[0022] In this application, the use of the singular includes the plural, and the plural encompasses the singular, unless otherwise specified. For example, although the specification refers to "a" coating or "an" filler material, combinations (i.e., a plurality) of these components can be used.
[0023] Additionally, in this application, the use of "or" means "and / or" unless otherwise stated, even though "and / or" may be explicitly used in particular instances.
[0024] As used herein, terms such as "on," "onto," "applied on," "applied onto," "formed on," "deposited on," "deposited onto," and the like, mean formed, overlaid, deposited, or provided on, but not necessarily in contact with, a substrate surface. For example, a composition "applied onto" a substrate surface does not exclude the presence of one or more other intervening coating layers or films of the same or different compositions located between the composition and the substrate surface.
[0025] As used herein, "coating composition" refers to a composition, e.g., a mixture or dispersion, capable of producing a film, layer, etc., on at least a portion of a surface of a substrate.
[0026] As used herein, "powder coating composition" refers to a coating composition embodied in a solid particulate form, as opposed to a liquid form.
[0027] As used herein, the term "adhesive" refers to an adhesive that produces a load-bearing joint with a lap shear strength of greater than 3.0 MPa, measured according to ASTM D1002-10 using a 1.6 mm thick 2024-T3 aluminum substrate, as measured by an INSTRON 5567 machine in tension mode with a pull-up rate of 1.3 mm / min.
[0028] As defined herein, a "1K" or "one-component" coating composition is one in which all components may be premixed and stored, and in which the reactive components do not readily react under ambient or slight heat conditions, but instead react only upon activation by an external energy source. In the absence of activation from an external energy source, the composition remains largely unreacted (maintains sufficient processability in the uncured state, and maintains greater than 70% of the composition's initial lap shear strength in the cured state after storage for 8 months at 25°C). External energy sources that may be used to promote the curing reaction (i.e., crosslinking of the epoxy component and curing agent) include, for example, radiation (i.e., actinic radiation) and / or heat.
[0029] "Ambient" conditions generally refer to room temperature and humidity conditions, which can be from 10°C to 32°C and 20% relative humidity to 80% relative humidity, while slightly hot conditions are slightly above ambient temperature (e.g., 32°C to 35°C) but, in the case of 1K compositions, generally below the cure temperature of the coating composition, i.e., generally below which the reactive components will readily react and cure.
[0030] As used herein, the term "two-component" or "2K" refers to a composition in which at least some of the reactive components readily associate to form interactions or react to form bonds (physically or chemically) and when mixed, at least partially cure without activation from an external energy source, such as ambient or slight thermal conditions. Those skilled in the art will appreciate that the two components of the composition are stored separately from each other and mixed immediately prior to application of the composition. The two-component composition may be heated or baked as needed, as described below.
[0031] As used herein, the term "cure" or "curing" means that the components forming the composition are crosslinked to form a material such as a coating, layer, pottant, pad, etc. As used herein, the term "at least partially cured" means that at least a portion of the components forming the composition have interacted, reacted, and / or crosslinked to form a material. The composition is at least partially cured or hardened when the components of the composition are mixed, resulting in at least partial reaction of reactive functional groups of the components of the composition.
[0032] For example, the term "curable" as used in connection with a curable composition means that the indicated composition is polymerizable or crosslinkable through functional groups by means including, but not limited to, curing under ambient or slight thermal conditions and / or exposure to a catalyst.
[0033] By "ambient curable" it is meant that the composition undergoes a thermosetting reaction under room temperature and humidity conditions, e.g., without the aid of heat or other energy, e.g., baking in an oven, use of forced air, etc.
[0034] As used herein, unless otherwise indicated, the term "substantially free" means that the specified material is not intentionally added to the mixture or composition, respectively, and is present only as a trace impurity of less than 5% by weight, based on the total weight of the mixture or composition, respectively. As used herein, unless otherwise indicated, the term "essentially free" means that the specified material is present only in an amount of less than 2% by weight, based on the total weight of the mixture or composition, respectively. As used herein, unless otherwise indicated, the term "completely free" means that the mixture or composition, respectively, is free of the specified material, i.e., the mixture or composition contains 0% by weight of such material.
[0035] Coatings and Coated Substrates Disclosed herein is a coated substrate comprising a coating layer and an adhesive formed on at least a portion of the coating layer. As described in more detail below, the coating layer can be deposited from a powder coating composition and the adhesive can be deposited from an adhesive composition.
[0036] The coating layer may include a dielectric strength of at least 50 kV / mm, e.g., at least 60 kV / mm, measured using a Sefelec dielectric strength tester (RMG12AC-DC; voltage limits 12.0 kV DC, Imax limits 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) in accordance with ASTM D149-09. The coating layer may include a dielectric strength of no more than 120 kV / mm, e.g., no more than 100 kV / mm, measured using a Sefelec dielectric strength tester (RMG12AC-DC; voltage limits 12.0 kV DC, Imax limits 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) in accordance with ASTM D149-09. The coating layer may include a dielectric strength of 50 kV / mm to 120 kV / mm, e.g., 60 kV / mm to 100 kV / mm, measured using a Sefelec dielectric strength tester (RMG12 AC-DC; voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) in accordance with ASTM D149-09.
[0037] The coating layer may include a thermal conductivity of at least 0.3 W / Km, e.g., at least 0.35 W / Km, measured using a TIM heat resistance and conductivity measuring device (model LW-9389) according to ASTM D5470 (steady state method). The coating layer may include a thermal conductivity of 0.5 W / Km or less, e.g., 0.45 W / Km or less, measured using a TIM heat resistance and conductivity measuring device (model LW-9389) according to ASTM D5470 (steady state method). The coating layer may include a thermal conductivity of 0.3 W / Km to 0.5 W / Km, e.g., 0.35 W / Km to 0.45 W / Km, measured using a TIM heat resistance and conductivity measuring device (model LW-9389) according to ASTM D5470 (steady state method).
[0038] The coating layer may comprise a dielectric breakdown of at least 12 kV / mm, such as at least 15 kV / mm, such as at least 20 kV / mm, such as at least 25 kV / mm, such as at least 30 kV / mm, measured using a Sefelec dielectric strength tester (RMG12AC-DC; voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) in accordance with ASTM D149-09.
[0039] The powder coating composition can be applied by any means standard in the art, such as spraying, electrostatic spraying, fluidized bed processes, etc. The powder coating composition can also be applied in multiple applications on a substrate ("multi-application process"). For example, a first powder coating composition can be applied to at least a portion of the substrate. A second powder coating composition can be applied to at least a portion of the first coating composition. The first powder coating composition can be cured or at least partially cured, as needed, before applying the second powder coating composition. Alternatively, the second powder coating composition can be applied to at least a portion of the first coating composition. The first and second powder coating compositions can then be cured together at the same time.
[0040] It is understood that the powder coating composition can be cured with multiple types of heat sources, such as both convection heating and infrared radiation. For example, the powder coating composition can be partially cured with convection heating or infrared radiation and then fully cured with a different heat source selected from convection heating and infrared radiation.
[0041] In some examples, the powder coating composition can be cured with heat, such as convection heating, to a temperature range of 120°C to 260°C, e.g., 160°C to 240°C, e.g., 180°C to 200°C, for 1 to 40 minutes. The powder coating composition can also be cured with infrared radiation, where the peak metal temperature can reach 200°C to 260°C in about 10 seconds. High temperature ramping with infrared allows for rapid cure times. In some examples, the powder coating composition can be cured with infrared radiation to heat the composition to a temperature range of 140°C to 180°C, for 1 to 20 minutes.
[0042] Coatings formed from a single powder coating composition can be applied at any desired dry film thickness. For example, the dry film thickness can be at least 50 microns, such as at least 75 microns, such as at least 100 microns, and for example, the dry film thickness can be 300 microns or less, such as 250 microns or less, such as 200 microns or less. The dry film thickness can be 50 microns to 300 microns, such as 75 microns to 250 microns, such as 100 microns to 200 microns, such as 100 microns to 220 microns. When applying multiple powder coating compositions, it is understood that each composition can be applied to separately provide any of the aforementioned dry film thicknesses. For example, when applying two separate powder coating compositions, each individual powder coating composition can be applied at any of the aforementioned dry film thicknesses.
[0043] The adhesive may comprise a thermal conductivity of at least 0.7 W / Km, such as at least 0.8 W / Km, such as at least 0.9 W / Km, such as at least 1.0 W / Km, such as at least 1.5 W / Km, measured according to ASTM D5470 (Steady State Method) using a TIM Heat Resistance and Conductivity Measuring Instrument (Model LW-9389). The coating layer may comprise a thermal conductivity of 2.5 W / Km or less, such as 2.0 W / Km or less, measured according to ASTM D5470 (Steady State Method) using a TIM Heat Resistance and Conductivity Measuring Instrument (Model LW-9389). The coating layer may comprise a thermal conductivity of 0.7 W / Km to 2.5 W / Km, such as 0.8 W / Km to 2.5 W / Km, for example, 0.9 W / Km to 2.5 W / Km, such as 1.0 W / Km to 2.5 W / Km, for example, 1.5 W / Km to 2.5 W / Km, such as 0.7 W / Km to 2.0 W / Km, for example, 0.8 W / Km to 2.0 W / Km, for example, 0.9 W / Km to 2.0 W / Km, for example, 1.0 W / Km to 2.0 W / Km, for example, 1.5 W / Km to 2.0 W / Km, measured using a TIM heat resistance and conductivity measuring device (model LW-9389) according to ASTM D5470 (steady state method).
[0044] The adhesive may include a dielectric breakdown of at least 6 kV / mm, e.g., at least 6 kV / mm, measured according to ASTM D149-09 using a Sefelec dielectric strength tester (RMG12AC-DC; voltage limits 12.0 kV DC, Imax limits 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall). The adhesive may include a dielectric breakdown of 20 kV / mm or less, e.g., 17 kV / mm or less, measured according to ASTM D149-09 using a Sefelec dielectric strength tester (RMG12AC-DC; voltage limits 12.0 kV DC, Imax limits 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall). The adhesive may include a dielectric breakdown of 6 kV / mm to 20 kV / mm, e.g., 10 kV / mm to 17 kV / mm, measured using a Sefelec dielectric strength tester (RMG12 AC-DC; voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) in accordance with ASTM D149-09.
[0045] The adhesive may include a lap shear strength of at least 3 MPa, e.g., at least 8 MPa, measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up speed of 1 mm / min. The adhesive may include a lap shear strength of 30 MPa or less, e.g., 12 MPa or less, measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up speed of 1 mm / min. The adhesive may include a lap shear strength of 3 MPa to 30 MPa, e.g., 8 MPa to 12 MPa, measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up speed of 1 mm / min.
[0046] The adhesive composition may be applied by any means standard in the art, such as with a brush, roller, film, pellet, trowel, spatula, dip, spray gun, and applicator gun, to form a coating on at least a portion of the coating. The adhesive is typically formed when the composition deposited on at least a portion of the substrate surface is allowed to at least partially dry or cure by methods known to those skilled in the art (e.g., under ambient conditions or by exposure to thermal heating).
[0047] For example, the adhesive composition may be allowed to cure at room temperature or under slightly thermal conditions, and / or the composition may be cured by baking and / or curing at elevated temperatures, e.g., 180° C. or less, e.g., 130° C. or less, e.g., 110° C. or less, e.g., 100° C. or less, e.g., 90° C. or less, e.g., 80° C. or less, e.g., 70° C. or less, but greater than ambient, e.g., greater than 40° C., e.g., greater than 50° C., for any desired time (e.g., 5 minutes to 1 hour) sufficient to at least partially cure the composition on the substrate(s). Alternatively, the adhesive composition may be cured under ambient or slightly above ambient conditions, and, if desired, baked and / or further cured at elevated temperatures as described above.
[0048] The adhesive formed from the adhesive composition can be applied at any desired dry film thickness. For example, the dry film thickness can be at least 0.2 mm, such as at least 0.3 mm, such as at least 0.4 mm. The dry film thickness can be 3.0 mm or less, such as 1.5 mm or less, such as 1.0 mm or less. The dry film thickness can be 0.2 mm to 3.0 mm, such as 0.3 mm to 1.5 mm, such as 0.4 mm to 1.0 mm.
[0049] system Also disclosed herein is a system for coating a substrate comprising a powder coating composition and an adhesive composition. As described in more detail below, the powder coating composition can include an electrically insulating filler and the adhesive composition can include a thermally conductive filler.
[0050] Powder Coating Composition The coatings may be deposited from powder coating compositions comprising, consisting essentially of, or consisting of electrically insulating fillers and (meth)acrylate resins, polyurethanes, polyesters, polyamides, polyethers, polysiloxanes, epoxy resins, vinyl resins, copolymers thereof, and / or combinations thereof.
[0051] The powder coating composition includes a binder. The binder includes one or more film-forming resins that can be used to form a coating layer. The powder coating composition includes any of a variety of thermosetting powder coating compositions known in the art. The powder coating composition can also include a thermoplastic powder coating composition.
[0052] Non-limiting examples of suitable film-forming resins that form at least a portion of the binder of the powder coating composition include (meth)acrylate resins, polyurethanes, polyesters, polyamides, polyethers, polysiloxanes, epoxy resins, vinyl resins, copolymers thereof, and combinations thereof. As used herein, "(meth)acrylate" and similar terms refer to both the acrylates and the corresponding methacrylates. Furthermore, the film-forming resins can have any of a variety of functional groups, including, but not limited to, carboxylic acid groups, amine groups, epoxide groups, hydroxyl groups, thiol groups, carbamate groups, amide groups, urea groups, isocyanate groups (including blocked isocyanate groups), ethylenically unsaturated groups, and combinations thereof.
[0053] Thermosetting coating compositions typically include a crosslinking agent, which may be selected from any of the crosslinking agents known in the art, to react with the functionality of one or more film-forming resins used in the powder coating composition. Non-limiting examples of crosslinking agents include phenolic resins, amino resins, epoxy resins, triglycidyl isocyanurates, beta-hydroxy(alkyl)amides, alkylated carbamates, (meth)acrylates, salts of polycarboxylic acids with cyclic amidines, o-tolylbiguanides, isocyanates, blocked isocyanates, polyacids, anhydrides, organometallic acid-functional materials, polyamines, polyamides, aminoplasts, carbodiimides, oxazolines, and combinations thereof.
[0054] Suitable examples of resins useful in the powder coating compositions are discussed in PCT Publication No. 2021 / 173941(A1), paragraphs
[0006] to
[0042] ,
[0057] to
[0068] ,
[0088] to
[0105] , and
[0128] to
[0139] , which are incorporated herein by reference.
[0055] The electrically insulating filler may be a thermally conductive filler or a non-thermally conductive filler. As used herein, the term "electrically insulating filler" refers to a pigment, filler, or inorganic powder having a volume resistivity (measured according to ASTM D257, C611, or B193) of at least 10 Ω·m. For example, the electrically insulating filler may have a volume resistivity of at least 10 Ω.m (measured according to ASTM D257, C611, or B193), such as at least 20 Ω.m, such as at least 30 Ω.m, such as at least 40 Ω.m, such as at least 50 Ω.m, such as at least 60 Ω.m, such as at least 60 Ω.m, such as at least 70 Ω.m, such as at least 80 Ω.m, such as at least 80 Ω.m, such as at least 90 Ω.m, such as at least 100 Ω.m.
[0056] The electrically insulating filler may include a thermally conductive electrically insulating filler material. As used herein, the term "thermally conductive electrically insulating filler" or "TC / EI filler" means a pigment, filler, or inorganic powder having a thermal conductivity (measured according to ASTM D7984) of at least 5 W / mK at 25° C. and a volume resistivity (measured according to ASTM D257, C611, or B193) of at least 10 Ω.m. The TC / EI filler material may include organic or inorganic materials, may include particles of a single type of filler material, or may include particles of two or more types of TC / EI filler materials. That is, the TC / EI filler material may include particles of a first TC / EI filler material and may further include particles of at least a second (i.e., second, third, fourth, etc.) TC / EI filler material different from the first TC / EI filler material. As used herein with respect to types of filler materials, references to "first," "second," etc. are for convenience only and do not refer to an order of addition or the like.
[0057] The TC / EI filler material may have a thermal conductivity of at least 5 W / mK (measured according to ASTM D7984), such as at least 18 W / mK, such as at least 55 W / mK, at 25° C. The TC / EI filler material may have a thermal conductivity of at least 3,000 W / mK or less (measured according to ASTM D7984), such as at most 1,400 W / mK, such as at most 450 W / mK, at 25° C. The TC / EI filler material may have a thermal conductivity of from 5 W / mK to 3,000 W / mK (measured according to ASTM D7984), such as from 18 W / mK to 1,400 W / mK, such as from 55 W / mK to 450 W / mK, at 25° C.
[0058] The TC / EI filler material may have a volume resistivity of at least 10 Ω.m (measured according to ASTM D257, C611, or B193), such as at least 20 Ω.m, for example at least 30 Ω.m, such as at least 40 Ω.m, for example at least 50 Ω.m, such as at least 60 Ω.m, for example at least 60 Ω.m, such as at least 70 Ω.m, for example at least 80 Ω.m, such as at least 80 Ω.m, for example at least 90 Ω.m, such as at least 100 Ω.m.
[0059] Suitable non-limiting examples of TC / EI filler materials include nitrides, metal oxides, semi-metal oxides, metal hydroxides, arsenides, carbides, minerals, ceramics, and diamond. For example, the TC / EI filler material can comprise, consist essentially of, or consist of boron nitride, silicon nitride, aluminum nitride, boron arsenide, aluminum oxide, magnesium oxide, dead-burned magnesium oxide, beryllium oxide, silicon dioxide, titanium oxide, zinc oxide, nickel oxide, copper oxide, tin oxide, aluminum hydroxide (i.e., aluminum trihydrate), magnesium hydroxide, boron arsenide, silicon carbide, agate, emery, ceramic microspheres, diamond, or any combination thereof. Non-limiting examples of commercially available TC / EI filler materials of boron nitride include, for example, CarboTherm from Saint-Gobain, CoolFlow and PolarTherm from Momentive, and hexagonal boron nitride powder available from Panadyne; non-limiting examples of aluminum nitride include, for example, aluminum nitride powder available from Micron Metals Inc., and Toyalnite from Toyal; non-limiting examples of aluminum oxide include, for example, Microgrit from Micro Abrasives, Nabalox from Nabaltec, Aeroxide from Evonik, and Alodur from Imerys; non-limiting examples of dead-burned magnesium oxide include, for example, MagChem® P98 from Martin Marietta Magnesia Specialties; non-limiting examples of aluminum hydroxide include, for example, APYRAL from Nabaltec GmbH and aluminum hydroxide from Sibelco, and non-limiting examples of ceramic microspheres include, for example, Zeeospheres Examples of fillers include ceramic microspheres from Ceramics or 3M. These fillers can also be surface-modified. For example, surface-modified magnesium oxide available as PYROKISUMA 5301K available from Kyowa Chemical Industry Co., Ltd.Alternatively, the TC / EI filler material may not include any surface modifications.
[0060] As used herein, the term "dead-burned magnesium oxide" refers to magnesium oxide that has been calcined at high temperatures (e.g., in the range of 1500°C to 2000°C in a high temperature shaft kiln) to yield a material that is very less reactive compared to uncalcined magnesium oxide.
[0061] The TC / EI filler material may be included as a single TC / EI filler material or may be included as a combination of two or more of the above-mentioned TC / EI filler materials.
[0062] Electrically insulating fillers may include non-thermally conductive electrically insulating filler materials. As used herein, the term "non-thermally conductive electrically insulating filler" or "NTC / EI filler" means a pigment, filler, or inorganic powder having a thermal conductivity of at least 5 W / mK (measured according to ASTM D7984) at 25° C. and a volume resistivity of at least 10 Ω.m (measured according to ASTM D257, C611, or B193). For example, the NTC / EI filler may have a thermal conductivity at 25° C. of less than 5 W / mK (measured according to ASTM D7984, such as 3 W / mK or less, such as 1 W / mK or less, such as 0.1 W / mK or less, such as 0.05 W / mK or less. For example, the NTC / EI filler may have a volume resistivity of at least 10 Ω.m (measured according to ASTM D257, C611, or B193), such as at least 20 Ω.m, such as at least 30 Ω.m, such as at least 40 Ω.m, such as at least 50 Ω.m, such as at least 60 Ω.m, such as at least 60 Ω.m, such as at least 70 Ω.m, such as at least 80 Ω.m, such as at least 80 Ω.m, such as at least 90 Ω.m, such as at least 100 Ω.m. The NTC / EI filler material may be organic or inorganic.
[0063] Suitable non-limiting examples of NTC / EI filler materials include, but are not limited to, mica, silica, wollastonite, barium sulfate, calcium carbonate, glass microspheres, clay, or any combination thereof.
[0064] As used herein, the term "mica" generally refers to a layered silicate (phyllosilicate) mineral. Mica may include moscovite mica, which has the formula KAl 2 (AlSi 3 O 10 )(F,OH) 2 Or (KF) 2 (Al 2 O 3 ) 3 (SiO 2 ) 6 (H 2 O) aluminum and potassium phyllosilicate minerals. Exemplary, non-limiting commercially available moscovite micas include products sold under the trade name DakotaPURE™ available from Pacer Minerals, such as DakotaPURE™ 700, DakotaPURE™ 1500, DakotaPURE™ 2400, DakotaPURE™ 3000, DakotaPURE™ 3500, and DakotaPURE™ 4000.
[0065] Silica (SiO 2) may include fumed silica, which includes silica that has been treated with a flame to form a three-dimensional structure. The fumed silica may be untreated or may be surface treated, for example, with a siloxane, such as polydimethylsiloxane. Exemplary non-limiting commercially available fumed silicas include products sold under the trade name AEROSIL® available from Evonik Industries, such as AEROSIL® R104, AEROSIL® R106, AEROSIL® R202, AEROSIL® R208, AEROSIL® R972, and products sold under the trade name HDK® available from Wacker Chemie AG, such as HDK® H17 and HDK® H18.
[0066] Wollastonite is a calcium inosilicate mineral (CaSiO ) that may contain small amounts of iron, aluminum, magnesium, manganese, titanium, and / or potassium. 3 For example, wollastonite is 1.5 to 2.1 m 2 / g, e.g. 1.8m 2 / g and a median particle size of 6 microns to 10 microns, e.g., 8 microns. A non-limiting example of a commercially available wollastonite includes NYAD 400 available from NYCO Minerals, Inc.
[0067] Calcium carbonate (CaCO 3) may include precipitated or ground calcium carbonate. The calcium carbonate may be surface treated with stearic acid or may not be surface treated. Non-limiting examples of commercially available precipitated calcium carbonate include Ultra-Pflex®, Albafil®, and Albacar HO® available from Specialty Minerals, and Winnofil® SPT available from Solvay. Non-limiting examples of commercially available ground calcium carbonate include Duramite™ available from IMERYS and Marblewhite™ available from Specialty Minerals.
[0068] Useful clay minerals include non-ionic plate-like fillers such as talc, pyrophyllite, chlorite, vermiculite, or combinations thereof.
[0069] The glass microspheres can be hollow borosilicate glass. Non-limiting examples of commercially available glass microspheres include 3M Glass Bubbles types VS, K series, and S series available from 3M.
[0070] The electrically insulating filler material may have any particulate or geometric shape. For example, the electrically insulating filler material may be of regular or irregular shape, such as spherical, ellipsoidal, cubic, plate-like, acicular (elongated or fibrous), rod-like, disk-like, prismatic, flaky, rock-like, aggregates thereof, and any combination thereof.
[0071] The particles of the electrically insulating filler material may have an average particle size reported in at least one dimension, as reported by the manufacturer, of at least 0.01 microns, such as at least 2 microns, for example at least 10 microns. The particles of the electrically insulating filler material may have an average particle size reported in at least one dimension, as reported by the manufacturer, of 500 microns or less, such as 300 microns or less, 200 microns or less, 150 microns or less. The particles of the electrically insulating filler material may have an average particle size reported in at least one dimension, as reported by the manufacturer, of 0.01 microns to 500 microns, such as 0.1 microns to 300 microns, for example 2 microns to 200 microns, for example 10 microns to 150 microns. A suitable method for measuring the average particle size includes measurements using an instrument such as a Quanta 250 FEG SEM or equivalent.
[0072] The particles of the electrically insulating filler material of the powder coating composition may have a reported Mohs hardness (based on the Mohs hardness scale) of at least 1, such as at least 2, such as at least 3. The particles of the electrically insulating filler material of the powder coating composition may have a reported Mohs hardness of 10 or less, such as 8 or less, such as 7 or less. The particles of the electrically insulating filler material of the powder coating composition may have a reported Mohs hardness of 1 to 10, such as 2 to 8, such as 3 to 7.
[0073] The powder coating composition may comprise the electrically insulating filler material in an amount of at least 30% by weight, such as at least 45% by weight, such as at least 50% by weight, based on the total weight of the powder coating composition. The powder coating composition may comprise the electrically insulating filler material in an amount of 60% by weight or less, such as 55% by weight or less, such as 50% by weight or less, based on the total weight of the powder coating composition. The powder coating composition may comprise the electrically insulating filler material in an amount of 30% to 60% by weight, such as 45% to 55% by weight, such as 45% to 50% by weight, such as 50% to 55% by weight, based on the total weight of the powder coating composition.
[0074] The powder coating composition may include a flame retardant or a combination of flame retardants. For example, certain TC materials mentioned above, such as aluminum hydroxide and magnesium hydroxide, may also be flame retardants. As used herein, "flame retardant" refers to a material that slows or stops the spread of a fire or reduces its intensity. Flame retardants may be available as powders that can be mixed with the composition, foam, or gel. In an example, when a powder coating composition includes a flame retardant, such a composition may form a coating on a substrate surface, and such a coating may function as a flame retardant.
[0075] As described in more detail below, the flame retardant may include minerals, organic compounds, organic halogen compounds, organic phosphorus compounds, or combinations thereof. Suitable examples of minerals include huntite, hydromagnesite, various hydrates, red phosphorus, boron compounds such as borates, carbonates such as calcium carbonate and magnesium carbonate, and combinations thereof. Suitable examples of organic halogen compounds include organic chlorines, such as chlorendic acid derivatives and chlorinated paraffins, organic bromines, such as decabromodiphenyl ether (decaBDE), decabromodiphenyl ethane (a substitute for decaBDE), polymeric brominated compounds, such as brominated polystyrene, brominated carbonate oligomers (BCO), brominated epoxy oligomers (BEO), tetrabromophthalic anhydride, tetrabromobisphenol A (TBBPA), and hexabromocyclododecane (HBCD). Such halogenated flame retardants may be used in conjunction with synergists to enhance their efficiency. Other suitable examples include antimony trioxide, antimony pentoxide, and sodium antimonate. Suitable examples of organophosphorus compounds include triphenyl phosphate (TPP), resorcinol bis(diphenyl phosphate) (RDP), bisphenol A diphenyl phosphate (BADP), and tricresyl phosphate (TCP); phosphonates, such as dimethyl methyl phosphonate (DMMP); and phosphinates, such as aluminum diethyl phosphinate. In one important class of flame retardants, the compounds contain both phosphorus and halogens. Such compounds include tris(2,3-dibromopropyl)phosphate (brominated tris) and chlorinated organic phosphates, such as tris(1,3-dichloro-2-propyl)phosphate (chlorinated tris or TDCPP) and tetrakis(2-chloroethyl)dichloroisopentyl diphosphate (V6). Suitable examples of organic compounds include carboxylic acids, dicarboxylic acids, melamine, and organic nitrogen compounds. Other suitable flame retardants include ammonium polyphosphate and barium sulfate.
[0076] Adhesive Composition The adhesive may be deposited from an adhesive composition that comprises, consists essentially of, or consists of a thermally conductive filler and a compound containing electrophilic functional groups, a thiol-terminated compound, a thermoplastic polymer, or any combination thereof.
[0077] The adhesive composition can be a one-component adhesive composition, a two-component composition, or a multi-component composition (ie, more than two components).
[0078] Suitable electrophilic functional groups useful in the adhesive compositions disclosed herein include epoxide, carbonate, isocyanate, keto, aziridine, thiirane, cyclic lactone, and carbodiimide functional groups. The adhesive composition may further include a second compound comprising a nucleophilic functional group. The second molecule may be monofunctional or polyfunctional. The second molecule may be a monomer, a small molecule, or a polymer. Suitable nucleophilic functional groups include active hydrogen functional groups, including amine, hydroxy, thiol, carboxy, anhydride, acetoacetate (ACAC) functional groups, and combinations thereof. Suitable molecules comprising nucleophilic functional groups may include amines, thiols, alcohols, polyols, carboxylic acids, anhydrides, or combinations thereof. The nucleophilic functional groups may be blocked, unblocked, encapsulated, or unencapsulated.
[0079] Suitable thiol-terminated compounds that can be used in the adhesive composition include monomers, polymers, and / or oligomers.
[0080] The composition may include thermoplastic polymer.Suitable thermoplastic polymers include polyamides such as nylon and aramid; polyolefins such as polybutadiene, polyisobutylene, polybutene, polymethylpentene, amorphous polypropylene, polyethylene terephthalate, polyethylene, polystyrene, ethylene propylene copolymers, polyvinyl chloride, and vinyl chloride copolymers; polyurethane; styrene block copolymers such as styrene-butadiene, styrene-isoprene, styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene / butylene-styrene, styrene-ethylene / propylene; polyethers such as polyethylene oxide, polypropylene oxide, polyoxymethylene, poly(p-phenylene ether); ethylene-vinyl acetate; polybenzimidazole; polyphenylsulfide; polyethersulfone; polyetheretherketone; chloroprene; acrylonitrile butadiene; polycarbonate; polyacrylates such as poly(meth)acrylates, or combinations thereof. In examples, useful non-reactive elastomers include Polyvest® polybutadiene available from Evonik. Examples of reactive elastomers include Hypro® ATBN amine-functional butadiene copolymers available from Emerald Performance Materials. Suitable examples of thermoplastic elastomers include olefinic thermoplastic elastomers, polyether block amide polybutadiene thermoplastic elastomers, polyester thermoplastic elastomers, styrene thermoplastic elastomers, and vinyl thermoplastic elastomers, as well as rubbers such as butadiene rubber, butyl rubber, bromobutyl rubber, chlorobutyl rubber, polyisobutylene rubber, chlorosulfonate polyethylene rubber, epichlorohydrin rubber, ethylene-propylene rubber, fluoroelastomers (vinylidene fluoride-hexafluoropropylene copolymers), natural rubber, neoprene rubber, nitrile rubber, polysulfide rubber, polyurethane rubber, silicone rubber, and styrene-butadiene rubber.
[0081] The adhesive composition may include a hydrolyzable component. The hydrolyzable component may include a silane-containing polymer, a silyl-containing polymer, an imine, or a combination thereof. The silane-containing polymer may include a polythioether, a polyester, a polyether, a polyisocyanate, a poly(meth)acrylate, a polyolefin, a polyurea, a polyurethane, or a combination thereof. The silane-containing polymer may include an alkoxy group, an acyloxy group, a halogen group, an amino group, or a combination thereof. The silyl-containing polymer may include an alkyl group, a phenyl group, or a combination thereof. The silyl-containing polymer may include a polythioether, a polysulfide, a thiol ester, a thiol polyacrylate, or a combination thereof. The imine may include a ketimine, an aldimine, or a combination thereof.
[0082] The adhesive composition may optionally include any of a variety of accelerators, elastomeric particles, additives, plasticizers, solvents, etc. known in the art.
[0083] Suitable examples of compounds useful in the adhesive composition are described in PCT Publication No. 2021 / 211694(A1), paragraphs
[0022] to
[0046] ,
[0055] to
[0059] ,
[0062] to
[0138] ,
[0204] , and
[0206] ; PCT Publication No. 2021 / 211184(A1), paragraphs
[0019] to
[0035] ,
[0044] to
[0051] ,
[0056] ,
[0061] to
[0080] ,
[0110] to
[0127] ,
[0135] to
[0141] ,
[0144] to
[0146] , and
[0150] to
[0152] ; PCT Publication No. 2021 / 211 183(A1), paragraphs
[0017] to
[0030] ,
[0040] to
[0043] ,
[0046] to
[0050] ,
[0081] to
[0093] ,
[0101] to
[0107] , and
[0111] to
[0113] ; and PCT Publication No. 2021 / 211722(A1), paragraphs
[0018] to
[0035] ,
[0044] to
[0056] ,
[0061] ,
[0062] ,
[0068] to
[0172] ,
[0203] to
[0225] ,
[0233] to
[0240] , and
[0245] , all of which are incorporated herein by reference.
[0084] The adhesive composition may include a thermally conductive filler. The thermally conductive filler may be an electrically insulating filler. Suitable TC / EI fillers include any of those described above for the powder coating composition.
[0085] The thermally conductive filler may be present in the adhesive composition in an amount of at least 60% by weight, for example at least 75% by weight, based on the total weight of the adhesive composition. The thermally conductive filler may be present in the adhesive composition in an amount of up to 90% by weight, for example up to 86% by weight, based on the total weight of the composition. The thermally conductive filler may be present in the adhesive composition in an amount of 60% to 90% by weight, for example 75% to 86% by weight, based on the total weight of the adhesive composition.
[0086] The adhesive composition may further comprise a non-thermally conductive, electrically insulating filler. Suitable NTC / EI fillers useful in the adhesive composition include any of the NTC / EI fillers described above with respect to the powder coating composition.
[0087] The adhesive composition may further comprise a flame retardant. Suitable flame retardants for use in the adhesive composition include any of the flame retardants described above with respect to the powder coating composition.
[0088] Base material The substrate may be selected from a wide variety of substrates and combinations thereof. Non-limiting examples of substrates include automotive substrates. vehicle , industrial substrates, marine substrates and components such as ships, vessels, and land and offshore equipment, storage tanks, packaging substrates, building substrates, aircraft and aerospace components, power storage devices, batteries and battery components, bus bars, metal wire, copper or aluminum conductors, nickel conductors, wood flooring and furniture, fasteners, coiled metal, heat exchangers, vents, extrusions, roofing, wheels, grates, belts, conveyors, grain or seed silos, wire mesh, bolts or nuts, screens or grids, HVAC equipment, frames, tanks, cords, wires, apparel, electronic devices and components including housings and circuit substrates, glass, sporting goods including golf balls, stadiums, buildings, bridges, containers such as food and beverage containers, and the like.
[0089] Substrates, including any of the aforementioned substrates, can be metallic or non-metallic. Metallic substrates include, but are not limited to, tin, steel, cold rolled 61 steel, hot rolled steel, zinc metal coated steel, zinc compounds, zinc alloys, electrogalvanized steel, hot dip galvanized steel, galvanneal steel, galvalume, zinc alloy plated steel, stainless steel, zinc-aluminum-magnesium alloy coated steel, zinc-aluminum alloy, aluminum, aluminum alloy, aluminum plated steel, aluminum alloy plated steel, zinc-aluminum alloy coated steel, magnesium, magnesium alloy, nickel, nickel plated, bronze, tin plated, tin plated, clad, titanium, brass, copper, silver, gold, 3D printed metals, cast or forged metals and alloys, or combinations thereof.
[0090] As used herein, " vehicle " or variations thereof, civilian, commercial, and military aircraft, and / or planes, helicopters, automobiles, motorcycles, trucks, and / or bicycles, e.g., land-based e-bikes. vehicle The shape of the substrate may be in the form of a sheet, plate, bar, rod, or any desired shape.
[0091] As mentioned above, the substrate may include a battery or a battery component. vehicle The battery component may be an electric vehicleThe battery components may include, but are not limited to, a battery cell, a battery shell, a battery module, a battery pack, a battery box, a battery cell casing, a pack shell, a battery lid and tray, a thermal management system, an inverter, a battery housing, a module housing, a module racking, a battery side plate, a battery cell enclosure, a cooling module, a cooling tube, a cooling fin, a cooling plate, a bus bar, a battery frame, an electrical connection, a metal wire, a copper or aluminum conductor or cable, any part of a stationary energy storage system, or any combination thereof.
[0092] As mentioned above, the adhesive coating compositions and powder coating compositions may be applied to any of these substrates to form an electrically insulating coating (i.e., a dielectric coating), a thermally conductive coating, or an electrically insulating and thermally conductive coating, as described herein.
[0093] As shown in Figures 1-9, a coating layer can be deposited on a surface of a substrate from one of the powder coating compositions disclosed herein. An adhesive can be formed by applying one of the adhesive compositions disclosed herein to at least a portion of the coating layer such that the adhesive is between the coating layer and the surface of a second substrate.
[0094] 1-9 show non-limiting examples of battery assembly components and structures, as well as non-limiting applications or uses of the compositions disclosed herein in such battery assemblies. Although FIGS. 1-9 show specific examples of cell shapes and cell arrangements, the cells may be arranged in any configuration known to one of skill in the art. Additionally, the cured compositions may be used to form pads, adhesives, coatings, pottants, and the like to provide thermal protection between battery cells, within battery modules, and / or within battery packs. These materials may be used on any surface or in any space within such battery assemblies. For example, the compositions disclosed herein may also be useful in battery assemblies, including, but not limited to, cell-to-module (FIGS. 3, 4, 6B), module-to-pack (FIG. 6C, 7), cell-to-pack (FIG. 8), and cell-to-chassis battery assemblies (FIG. 9). Such battery assemblies may be used in any of the aforementioned applications, but not limited to these.
[0095] A battery assembly can be any combination of one or more battery cells, interconnects that provide electrical conductivity therebetween, and supporting components such as, by way of non-limiting example, control electronics and components that ensure the structural, mechanical, and environmental requirements necessary for the operation of a particular battery (e.g., but not limited to, cell interconnects such as wires, battery pack enclosures including trays and lids, module enclosures, module frames and frame plates, module racks, cooling and heating components including cooling plates, cooling fins, and cooling tubes, electrical bus bars, battery management systems, battery thermal management systems, chargers, inverters and converters).
[0096] Battery cells 10 are generally single-unit energy storage containers that can be connected in series or in parallel. Battery cells may be of any suitable size or shape known to those skilled in the art, such as, but not limited to, cylindrical (FIGS. 1, 4, and 9), prismatic (FIGS. 2, 5-8), and / or pouch (FIG. 3). Battery cells 10 are enclosed to provide the desired mechanical protection and environmental isolation of the cells. For example, cylindrical and prismatic cells may be enclosed in metal cans, cases, and lids, while pouch cells may be enclosed in multi-layer laminate foils. Battery terminals 1 connect the electrodes within the battery cells, one positive terminal and the other negative terminal, to an electrical circuit outside the battery cells. As shown in FIG. 4, battery cells 10 may be connected in series or parallel with other battery cells 10 by interconnector wires 5 to allow electrical current to flow between the cells 10.
[0097] As shown in Figures 3, 4, 5, 6B, 6C, and 7, the battery cells 10 may be arranged into a module 100 including multiple cells 10 connected in series or parallel. The module 100 may include a partial enclosure of the arranged cells 10. Ancillary components such as those previously described may be included. Voids of any size may be located between the multiple cells, the ancillary components, the base, and / or any interior surface of the module wall or other enclosure 120.
[0098] 1 shows a top down view of a cylindrical battery cell 10 with terminals 1. As shown, the cells are arranged in a row with either cooling tubes 3 or dielectric and thermal insulation paper (insulating paper) 4 between them. As shown, materials such as powder coatings and adhesives 6 formed from compositions disclosed herein can be disposed between the cells 10, cooling tubes 3, and / or insulating paper 4, respectively.
[0099] 2 shows an exploded isometric view of an array of prismatic battery cells 10. As shown, each prismatic cell 10 can include a top 11, a bottom, and a wall 13 disposed between the top and bottom, each having a surface. As shown, a coating (i.e., powder coating and adhesive) 8 formed from a composition disclosed herein can be disposed between the surfaces of the cell walls 13 of adjacent cells 10.
[0100] 3 shows a cutaway front view of an array of pouch battery cells 10 in a module 100. A module wall 120 may partially encase the cells 10. As shown, a material such as a coating (i.e., powder coating and adhesive) 8 formed from a composition disclosed herein may be disposed between the surfaces of the cells 10.
[0101] FIG. 4 shows an isometric view of cylindrical cells 10 in a battery module 100. Each cell may include a top 11, a bottom 12, and a wall 13 disposed between the top and bottom, each having a surface. The top 11 and bottom 12 may be oppositely charged terminals, one positive terminal 1 and the other negative terminal (not shown). The battery cells may be connected at their terminals by interconnectors, such as wires 5, to allow electrical current to flow between the electrical cells. The module 100 or module walls 120 may form a void having a volume. The cells 10 may be disposed within the void to consume a portion of the volume. Materials, such as powder coatings and adhesives 7 formed from compositions disclosed herein, may be disposed within the void to consume a portion of the volume, such that the materials are adjacent to the surface of the cell wall 13 and / or the interior surface of one of the walls 120 of the module 100.
[0102] 5 shows an exploded perspective view of a battery module 100 comprised of one or more arrays of battery cells 10, cooling fins 230, and / or cooling plates 240. Materials such as coatings (i.e., powder coatings and adhesives) 8 formed from compositions disclosed herein may be disposed between the cells 10. Additional coatings 8 may be disposed between the cells 10, cooling fins 230, and / or cooling plates 240. Additional coatings may be disposed between the battery cell array and the inner surface of the wall 120. Another coating 8 may be disposed adjacent to the outer surface of the wall 120.
[0103] 6 shows an isometric view of a battery assembly from a battery cell 10 (FIG. 6A) to a battery module 100 (FIG. 6B) to a battery pack 200 (FIG. 6C). The battery module 100 includes a plurality of battery cells 10, and the battery pack 200 includes a plurality of battery modules 100.
[0104] 7 shows a perspective view of a cut-out of a battery pack 200. The battery pack includes a plurality of battery modules 100 and cells 10 within each module 100. The base of the battery pack 200 includes a cooling plate 240. Materials 9, such as powder coatings and adhesives formed from compositions disclosed herein, can be disposed between the cooling plate 240 and the inner surface of the wall of the battery pack 200. Materials 8, such as powder coatings and adhesives formed from compositions disclosed herein, can be disposed between the cells 10 within the modules 100.
[0105] 8 shows an isometric view of the cells 10 into a battery pack 200 assembly. The cells 10 are arranged in the pack 200 (without being in a separate module).
[0106] In other cases, the battery cells may be arranged on or in an article, such as, but not limited to, a cell-to-chassis battery assembly, as shown in Figure 9, where one or more cells are used to build a battery assembly without pre-assembling the cells into modules and / or packs. Figure 9 shows an isometric cut-out view of a cell-to-chassis battery assembly 300. The cells 10 are arranged on a base that includes a substructure 55, vehicle By frame 45, vehicle It is supported below the interior floor 35 .
[0107] Any battery assembly may further include a thermal management system (not shown) including air or fluid circuits that may be liquid based (e.g., glycol solution) or direct refrigerant based. Flame retardant materials may be adjacent to any of these components of the battery assembly.
[0108] Surprisingly, it has been discovered that the coated substrate can have a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured using a TIM Heat Resistance and Conductivity Measuring Instrument (Model LW-9389) according to ASTM D5470 (Steady State Method).
[0109] The following examples are for illustrative purposes only and are not to be construed as limiting. EXAMPLES
[0110] Powder Coating Composition In Example 1, 0.6 grams of carbon black, 25.44 grams of barium sulfate, and 0.15 grams of aluminum oxide were added to an epoxy-containing powder coating composition crosslinked with a phenolic hardener. In Example 2, 0.6 grams of carbon black, 50 grams of aluminum trihydroxide, and 0.15 grams of aluminum oxide were added to an epoxy-containing powder coating composition crosslinked with a phenolic hardener.
[0111] The electrically insulating filler was incorporated into the chips of the powder coating composition. The chips were then milled in a Dongyuan ACM®-05 air classifier mill to obtain a fine powder, followed by tap sieving through 160 mesh to achieve a final particle size in the range of 5 to 100 microns, with the majority of the particles being 30 to 52 microns in volume. The resulting coating compositions for each of Examples 1 and 2 were free-flowing solid particulate powder coating compositions.
[0112] Dielectric performance evaluation Each of the powder coating compositions of Examples 1 and 2 was electrostatically applied onto an aluminum substrate (Alloy 3003 on AQT-412 panels, bare mill finish from Q-LAB) using an Encore Nordson powder coating cup gun equipped with a 3 mm flat spray nozzle with the following parameters: 60 kV voltage, 20 μA amperage limit, 10 psi atomization, and 10 psi delivery air flow.
[0113] To test the breakdown voltage, coatings with a dry film thickness of 150-200 μm were formed on aluminum panels from the powder coating compositions of Examples 1 or 2. The panels were baked at 190° C. for 20 minutes and then cooled at room temperature to obtain the final samples. The breakdown voltage of each sample was measured using a Sefelec dielectric strength tester RMG12AC-DC according to ASTM D149-09 Breakdown Voltage and Dielectric Strength Test. The measurements employed the following parameters: voltage limit 12.0 kV DC, Imax limit: 0.1 mA, 10 sec ramp, 20 sec dwell, and 2 sec fall.
[0114] Specifically, the measurement included the following steps: (1) placing the specimen (coated aluminum panel) in the electrical insulation box of the dielectric strength tester and placing it on the brass flat top cylinder electrical contact with the coated side of the specimen facing the contact, (2) lowering the convex tip of the brass and placing it on the back side of the specimen (opposite the coated side), then sealing the box, (3) running the dielectric strength tester three times and averaging the values (reported in Table 2).
[0115] Thermal conductivity evaluation Each of the powder coating compositions of Examples 1 and 2 was electrostatically applied onto an aluminum substrate (Alloy 3003 on AQT-412 panels, bare mill finish from Q-LAB) using an Encore Nordson powder coating cup gun equipped with a 3 mm flat spray nozzle with the following parameters: 60 kV voltage, 20 μA amperage limit, 10 psi atomization, and 10 psi delivery air flow.
[0116] To test thermal conductivity, powder coatings with dry film thickness of 100 μm, 160 μm, or 220 μm were formed on aluminum panels from the powder coating composition of Example 1 or 2. Powder coatings with thickness of either 160 μm or 220 μm were formed using a two-step application process to finally reach the desired coating thickness. All panels were baked at 190° C. for 20 minutes and then cooled at room temperature. The formed coatings were removed from the panels to obtain "free" films, which were cut into 26 mm*26 mm square samples for measurement.
[0117] The thermal conductivity of each sample was measured by TIM heat resistance and conductivity measuring instrument (model is LW-9389) according to ASTM D5470 (steady state method). The test results of the breakdown voltage and thermal conductivity of Examples 1 and 2 are summarized in Table 2. [Table 2]
[0118] Thermally Conductive Adhesives (TCA) In Example 3, 194.65 grams of aluminum oxide were added to Part A (the isocyanate-containing component) of the two-component polyurethane adhesive composition. Part B consisted of polyol and accelerators. In Example 4, 40 grams of aluminum oxide and 40 grams of aluminum hydroxide were added to Part A (the isocyanate-containing component) of the two-component polyurethane adhesive composition. Part B consisted of polyol and accelerators.
[0119] The method for preparing the TCA composition included:
[0120] (i) Dehydration of Thermally Conductive Fillers: Thermally conductive fillers S403Z and APYRAL 20X were dehydrated before use: S403Z and APYRAL 20X were weighed and placed in a 105° C. oven until the moisture content of each filler was less than 1000 ppm.
[0121] (ii) Mixing process of part A: The adhesive components and thermally conductive filler were weighed in a planetary stirring kettle and mixed in the kettle for 25 minutes with the stirring paddle speed of 35 RPM and the dispersion plate speed of 359 RPM. From 5 minutes of stirring, the kettle was evacuated to a vacuum degree of -0.99 to 1 via a vacuum pump. After stirring, the vacuum pump was turned off and nitrogen gas was introduced into the kettle to compensate for the air pressure balance. Mixture A was then removed from the kettle and packaged into cartridges by a press machine.
[0122] (iii) Mixing process of part B: The adhesive components were weighed in a planetary stirring kettle and mixed in the kettle for 25 minutes with the stirring paddle speed of 35 RPM and the dispersion plate speed of 359 RPM. From 5 minutes of stirring, the kettle was evacuated to a vacuum degree of -0.99 to 1 via a vacuum pump. After stirring, the vacuum pump was turned off and nitrogen gas was introduced into the kettle to compensate for the air pressure balance. Mixture B was then removed from the kettle and packaged into cartridges by a press machine.
[0123] Thermal conductivity evaluation The cartridges of parts A and B were applied on a PET film with a SULZER DP2X400 glue gun at 3-6 bar air pressure and covered with another PET film. The samples were placed in a tablet press to apply pressure, and a 0.2-3.0 mm thick frame was used as a spacer to control the thickness. After the films were fully cured, they were removed and the thermal conductivity was tested with a thermal conductivity tester according to ASTM D5470.
[0124] Two-tier system The powder coatings of Examples 1 and 2 were applied to the substrate (Al3003 panel) according to the same procedure as above, and the thermally conductive adhesive coatings of Examples 3 and 4 were applied on top of the powder coatings according to the same procedure as above. During the application of the thermally conductive adhesive coating, stainless steel balls with a diameter of 0.5 mm were used as spacers to control the thickness of the thermally conductive adhesive coating. Another Al3003 panel was covered with the thermally conductive adhesive coating, and a clamp was used to firmly bond the two Al3003 panels together until the coating was fully cured.
[0125] The lap shear strength of the thermally conductive adhesive was measured according to ASTM D1002-10 using a 2024-T3 aluminum substrate with a thickness of 1.6 mm, as measured by an INSTRON 5567 machine in tensile mode with a tensile speed of 1.3 mm / min. The adhesive strength was measured according to GB / T5210 by a universal tensile tester with a tensile speed of 5 mm / min, using an aluminum column with a size of 100*10*10 mm.
[0126] The heat resistance of the two-layer system was measured by a TIM heat resistance and conductivity measuring instrument (model is LW-9389) according to ASTM D5470 (steady state method). [Table 3]
[0127] These data demonstrate that the combination of a thermally conductive dielectric powder coating with a less thermally conductive adhesive resulted in a coating stack with good adhesive performance (lap shear and adhesive strength) and poor heat resistance (i.e., Example 2+3) compared to a more highly filled system (Example 2+4), which had poorer lap shear performance.
[0128] Although particular examples of the present disclosure have been described above for purposes of illustration, it will be apparent to those skilled in the art that many variations in the details of the disclosure can be made without departing from that which is set forth in the appended claims.
Claims
1. 1. A coated substrate comprising a coating layer and an adhesive formed on at least a portion of the coating layer, the coating layer being deposited from a powder coating composition and having a dielectric strength of at least 50 kV / mm measured in accordance with ASTM D149-09 (voltage limit 12.0 kV DC, Imax limit 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall) and at least 0.3 W / K measured in accordance with ASTM D5470 (steady state method). . m, the adhesive being formed from an adhesive composition comprising: (1) a thermally conductive filler; and (2) a compound comprising an electrophilic functional group, a thiol-terminated compound, a thermoplastic polymer, a hydrolyzable component, or any combination thereof, and the adhesive having a thermal conductivity of at least 0.7 W / K as measured according to ASTM D5470. . The coated substrate has a thermal conductivity of .mu.m.
2. 2. The coated substrate of claim 1, wherein the coating comprises a dielectric breakdown of at least 12 kV / mm measured according to ASTM D149-09 (voltage limits 12.0 kV DC, Imax limits 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall), the adhesive comprises a dielectric breakdown of at least 6 kV / mm measured according to ASTM D149-09 (voltage limits 12.0 kV DC, Imax limits 0.1 mA, 19 sec ramp, 20 sec dwell, 2 sec fall), and / or the adhesive comprises a lap shear strength of at least 3 MPa measured according to ASTM D1002-10 using an Instron 5567 machine in tension mode with a pull-up rate of 1 mm / min.
3. The coated substrate of claim 1, wherein the powder composition comprises an electrically insulating filler.
4. The coated substrate of claim 1 , wherein the substrate is part of an electrical storage device.
5. The coated substrate of claim 4 , wherein the electrical storage device comprises a battery or a battery component.
6. The coated substrate of claim 1 further comprising a second substrate in contact with the adhesive.
7. 2. The coated substrate of claim 1, wherein the coated substrate has a heat resistance of 2.0° C. / W or less, e.g., 0.5° C. / W to 2.0° C. / W, as measured according to ASTM D5470 (steady state method) using a TIM heat resistance and conductivity measuring instrument (Model LW-9389).
8. A battery comprising a battery cell and the coated substrate of claim 1.
9. The battery of claim 8 , wherein the battery cells and the coating are housed in a module.
10. The battery of claim 8 , wherein the battery and the coating are housed in a pack.
11. The battery of claim 9 , wherein the modules are housed in a pack.
12. The battery of claim 9 adjacent to a vehicle chassis.
13. The battery of claim 8 further comprising a battery component.
14. A vehicle comprising the battery of claim 8.
15. The vehicle of claim 14 , wherein the vehicle comprises a land vehicle, an aircraft, or a bicycle.
Citation Information
Patent Citations
Purintohaisenboodonoseizohoho
JP1976010368A
Method for forming thin layers in the manufacture of powder coatings and printed circuit boards
JP2006521434A
Thermally conductive and electrically insulating powder coating composition
JP2023516156A
Composition for powder coating materials and coated article
US20210062010A1
Composition for powder coating materials and coated article
WO2019044886A1